Mortalidade embrionária/fetal e abortos em suínos do Brasil - Antunes, João Marcelo Azevedo de Paula; Allendorf, Susan Dora; Appolinário, Camila Michele; Peres, Marina Gea; Vicente, Acácia Ferreira; Fonseca, Clóvis Reynaldo Silva; Demoner, Larissa de Castro; Megid, Jane [UNESP] (My University, 2012)
The objective was to evaluate the major infectious etiologies for embrionary/fetal mortality and abortion in pigs. Brazil is the world's fourth producer and third largest pork exporter. The causes of infectious abortion in swine are of the order of 40%, where the infections are the most important causes of reproductive disorders such as absorption, mummification, abortions, stillbirth and infertility. Due to high technification of swine in Brazil, a high density is found in animal farms, which lead to the virus are the main agents of reproductive disorders.

O objetivo deste trabalho foi levantar as principais causas infecciosas de mortalidade embrionária/fetal e abortos em suínos. O Brasil é o quarto produtor mundial de carne suína e o terceiro maior exportador. As causas infecciosas de problemas reprodutivos na suinocultura são da ordem de 40%, onde as infecções são as causas mais importantes de reabsorção, mumificação, abortamentos, natimortos e infertilidade. Devido à alta tecnificação da suinocultura no Brasil, uma alta densidade animal é encontrada nas granjas, o que levam aos vírus serem os principais agentes infecciosos envolvidos.
Embrionary/fetal mortality and abortion in pigs from Brazil
Keywords: Brazil; Swines; Infectious etiology; Abortion; Brasil; Suínos; Causas infecciosas; Abortamento